Transparent film, optical material comprising the same, and display device comprising the same

The transparent film, designed to satisfy specific relational equations for light waves, addresses the issue of color unevenness in flexible display devices, resulting in enhanced visibility and image quality.

JP2025069198APending Publication Date: 2025-04-30SK INNOVATION CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2025006444
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-08-09
Filing Date
2025-01-16
Publication Date
2025-04-30

AI Technical Summary

Technical Problem

Flexible display devices face issues with uneven color spots and image distortion due to the unevenness of polymer films produced through solution casting, leading to reduced display visibility.

Method used

A transparent film with specific optical properties is developed, where the phase relationship between two waves of transmitted light satisfies certain relational equations, minimizing color unevenness and ensuring excellent visibility in display devices.

Benefits of technology

The transparent film achieves excellent appearance quality with reduced optical fringes, providing clear image quality and improved visibility in flexible display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069198000001_ABST
    Figure 2025069198000001_ABST
Patent Text Reader

Abstract

To provide a transparent film and a display device comprising the same that suppress a color non-uniformity mura phenomenon in which a color is not uniform and appears as dots.SOLUTION: There is provided a transparent film in which light which is generated when one polarized light is transmitted through the film and in which two waves are mixed with each other satisfies the following relational expressions 1 and 2. [Relational expression 1] [Relational expression 2]SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent film, an optical material including the same, and a display device including the same. More specifically, the present invention relates to a transparent film having excellent optical properties such as visibility, an optical material including the same, and a display device including the same. [Background technology]

[0002] Flexible displays are attracting attention as next-generation display devices. The substrate material must be light, unbreakable, bendable, and easily processable without any shape restrictions.

[0003] In addition, glass substrates are currently used as substrate materials for display devices, but glass substrates are easily broken when subjected to external impacts, and are not only prone to damage when applied to display devices, but also have no flexibility, making them difficult to apply to flexible displays. Therefore, polymers, which are not only light but also unbreakable and can be manufactured into thin films, are attracting attention as the optimal material for realizing flexible displays.

[0004] When such a polymer is produced as a polymer film by a solution casting process, a mura phenomenon occurs during projection, which causes image distortion in a display device and reduces the overall visibility of the display.

[0005] Therefore, in order to improve display devices, it is necessary to improve the appearance quality of polymer films, which tend to deteriorate in visibility depending on specific angles or lights. Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a transparent film that suppresses the mura phenomenon, which is a phenomenon in which the color is not uniform and looks like spots, and a display device including the same.

[0007] In particular, the object is to provide a high-quality display device with clear image quality and excellent visibility. [Means for solving the problem]

[0008] In order to achieve the above object, the transparent film according to the present invention provides a mixed light of two waves generated when a polarized light is transmitted through the film, which satisfies the following relations 1 and 2. [Equation 1]

number

number

[0009] The transparent film according to one aspect of the present invention may be a polyimide film.

[0010] The transparent film according to one aspect of the present invention may have an average step height of the surface curvature of 1 to 1,000 nm.

[0011] The transparent film according to one embodiment of the present invention may have a curved area of ​​70% or less relative to the total surface area.

[0012] The transparent film according to one embodiment of the present invention may have a thickness of 20 to 200 μm.

[0013] The transparent film according to one aspect of the present invention may have a residual solvent content of 3% by weight or less based on the total weight of the film.

[0014] When drying the transparent film according to one embodiment of the present invention, the drying may be performed in a drying region including one or more nozzles selected from a perpendicular nozzle, a parallel flow nozzle, a venturi type nozzle, and the like.

[0015] Another aspect of the present invention is an optical material comprising the transparent film described above.

[0016] Yet another aspect of the present invention is a display device including the optical material described above. Effect of the Invention

[0017] The transparent film according to the present invention has the advantage of having excellent appearance quality without mottle caused by color unevenness.

[0018] Furthermore, the transparent film according to the present invention has an advantage that it can be used as a display device with excellent visibility due to reduced optical fringes.

[0019] Furthermore, the transparent film according to the present invention not only has excellent display quality, but also has the advantage that it has flexibility and can be provided as a flexible display device. [Brief description of the drawings]

[0020] [Figure 1] 4 is a photograph showing the appearance of transparent films according to an embodiment of the present invention and a comparative example observed with the naked eye when projecting the films. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention will be described in more detail below with reference to specific examples or embodiments including the accompanying drawings. However, the following specific examples or embodiments are merely references for describing the present invention in detail, and the present invention is not limited thereto, and may be realized in various forms.

[0022] In addition, unless otherwise defined, all technical and scientific terms have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs. The terms used in the description of the present invention are merely for the purpose of effectively describing specific embodiments and are not intended to limit the present invention.

[0023] Throughout the specification describing the present invention, when a part "comprises" a certain element, it means that the part may further include other elements, not excluding other elements, unless specifically stated to the contrary.

[0024] Also, as used in the specification and the appended claims, the singular forms "a," "an," and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0025] The inventors discovered that when light is transmitted through an optically transparent film and observed, if the phase relationship between the two waves satisfies a specific range, the unevenness phenomenon in which spots due to color unevenness occur does not occur, and the appearance quality and visibility are significantly improved, leading to the completion of the present invention.

[0026] In order to achieve the above object, the transparent film according to the present invention is characterized in that when a polarized light is transmitted through the film, the light containing two mixed waves generated satisfies the following relations 1 and 2.

[0027] [Equation 1]

number

[0028] [Equation 2]

number

[0029] In the above Relational Formulas 1 and 2, The T is the sum of the amplitudes when two waves of transmitted light interfere with each other, the A is the wave amplitude of polarized light, and the θ is the phase delay angle (°) of the wave that travels along the slow axis of the transparent film.

[0030] Specifically, in the transparent film of the present invention, when two waves having the same wavelength and amplitude emitted from a single light reach a single point via different paths, the phase relationship generated by the difference in the paths satisfies the above-mentioned relations 1 and 2.

[0031] In addition, the T according to the present invention may specifically be the sum of the magnitude W1 of the amplitude when two waves of the transmitted light cause constructive interference and the magnitude W2 of the amplitude when they cause destructive interference.

[0032] Specifically, the two waves transmitted through the optically anisotropic film have two travel speeds according to the polarization direction, which generates a phase difference, and the polarization direction in which the speed of light is fast is called the fast axis, and the polarization direction in which the speed of light is slow on the axis perpendicular to the fast axis is called the slow axis. Based on this, θ represents the phase delay angle of the wave traveling along the slow axis.

[0033] The transparent film according to the present invention may have optical anisotropy. As described above, due to the optical anisotropy of the transparent film, the two waves generated during transmission may have a phase difference, and the above-mentioned Relational Formulas 1 and 2 may be satisfied.

[0034] The transparent film according to the present invention satisfies the above-mentioned relational expressions 1 and 2, thereby minimizing the unevenness phenomenon that occurs due to color unevenness when white light is projected onto the transparent film, and has excellent appearance quality. Thus, the optical material and display device manufactured therefrom can provide excellent visibility.

[0035] According to one embodiment of the present invention, the relational expression 1 can preferably satisfy 0.92A to 1.08A, more preferably 0.95A to 1.05A. The relational expression 2 can preferably be less than 30°, more preferably less than 29°. When the relational expressions 1 and 2 are satisfied as described above, when white light is projected onto a transparent film, the unevenness phenomenon that causes spots due to color unevenness hardly occurs substantially, the image distortion phenomenon can be prevented, and excellent visibility can be achieved.

[0036] According to one embodiment of the present invention, the transparent film has transparency, and specifically, the total light transmittance measured using a Nippon Denshoku 300 in accordance with the ASTM E313 standard with a thickness of 30 to 80 μm as a standard may be 70 to 99%, preferably 80 to 99%, and more preferably 90 to 99%.

[0037] According to one aspect of the present invention, the transparent film may be a polyimide-based film, which has excellent transparency, heat resistance, chemical resistance, mechanical properties, electrical properties, dimensional stability, and the like, and is advantageous in terms of weight reduction, thinning, and flexibility, and is excellent for application to flexible display devices.

[0038] According to one aspect of the present invention, the polyimide-based film may be provided as a polyimide film including a polyimide resin derived and polymerized from a monomer mixture including a dianhydride and a diamine. The dianhydride and diamine are not particularly limited as long as they are commonly used and known substances.

[0039] According to one embodiment of the present invention, the diamine may be, for example, any one or a mixture of two or more selected from aliphatic diamines and aromatic diamines.

[0040] More specifically, the aromatic diamine is not particularly limited, but may be, for example, any one or a mixture of two or more selected from bistrifluoromethylbenzidine (TFDB), bis(3-aminophenyl)sulfone (3DDS), bis(4-aminophenyl)sulfone (4DDS), diaminophenyl ether, o-phenylenediamine (o-PDA), p-phenylenediamine (p-PDA), m-phenylenediamine (m-PDA), oxydianiline (ODA), methylenedianiline (MDA), bisaminophenylhexafluoropropane (HFDA), and 1,3-bis(4-aminophenoxy)benzene (TPE-R).

[0041] The aliphatic diamine is not particularly limited, and may be, for example, any one or a mixture of two or more selected from 1,4-diaminocyclohexane, 1,4-cyclohexanebis(methylamine), 4,4'-diaminodicyclohexylmethane (MCA), 4,4'-methylenebis(2-methylcyclohexylamine) (MMCA), ethylenediamine (EN), 1,3-diaminopropane (13DAP), tetramethylenediamine, 1,6-hexamethylenediamine (16DAH), and 1,12-diaminododecane (112DAD).

[0042] According to one embodiment of the present invention, the dianhydride may be any one or a mixture of two or more selected from aliphatic dianhydrides and aromatic dianhydrides.

[0043] More specifically, according to one embodiment of the present invention, the aromatic dianhydride may be, but is not limited to, any one or a mixture of two or more selected from the group consisting of 4,4'-hexafluoroisopropylidenediphthalic anhydride (6FDA), 1,2,4,5-benzenetetracarboxylic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), benzophenonetetracarboxylic dianhydride (BTDA), 4,4'-oxydiphthalic dianhydride (ODPA) and bisdicarboxyphenoxydiphenylsulfide dianhydride (BDSDA).

[0044] The aliphatic dianhydride is not particularly limited, and may be any one or a mixture of two or more selected from, for example, 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 5-(2,5-dioxotetrahydrofuryl)-3-methylcyclohexene-1,2-dicarboxylic dianhydride (DOCDA), bicyclooctene-2,3,5,6-tetracarboxylic dianhydride (BODA), 1,2,3,4-cyclopentanetetracarboxylic dianhydride (CPDA), 1,2,4,5-cyclohexanetetracarboxylic dianhydride (CHDA), 1,2,4-tricarboxy-3-methylcarboxycyclopentane dianhydride, and 1,2,3,4-tetracarboxycyclopentane dianhydride.

[0045] According to one embodiment of the present invention, the dianhydride can be copolymerized in an amount of 5 to 80 mol, preferably 10 to 70 mol, per 100 mol of the diamine.

[0046] When the dianhydride content is within the above range, a polyimide film having excellent visibility and optical properties can be provided.

[0047] The polyimide film manufactured from the above composition can suppress minute unevenness on the surface and minimize unevenness that occurs on the film.

[0048] According to one aspect of the present invention, the polyimide-based film may be provided as a polyamideimide film by further including an aromatic diacid dichloride in the monomer mixture in order to improve mechanical properties.

[0049] The aromatic diacid dichloride is not particularly limited, and may include, for example, any one or a mixture of two or more selected from terephthaloyl dichloride (TPC), isophthaloyl dichloride (IPC), 1,1'-biphenyl-4,4'-dicarbonyl dichloride (BPC), 1,4-naphthalenedicarboxylic dichloride (1,4-NaDC), 2,6-naphthalenedicarboxylic dichloride (2,6-NaDC), 1,5-naphthalenedicarboxylic dichloride (1,5-NaDC), etc. It is preferable to include any one or a mixture of two or more selected from terephthaloyl dichloride and isophthaloyl dichloride, etc.

[0050] In addition, the aromatic diacid dichloride is not limited to the above-mentioned examples, and may be used in combination with other acid halide compounds. However, it is preferable to use the aromatic diacid dichloride alone.

[0051] According to one embodiment of the present invention, the aromatic diacid dichloride can be copolymerized in an amount of 20 to 95 mol, preferably 30 to 90 mol, per 100 mol of diamine.

[0052] The polyamideimide film produced from the above composition not only has excellent mechanical properties and heat resistance, but also provides excellent display quality even at high temperatures and has optical properties that maintain high transparency.

[0053] According to one embodiment of the present invention, the dianhydride and the aromatic diacid dichloride may be contained in a molar ratio of 5:95 to 80:20, preferably in a molar ratio of 10:90 to 70:30.

[0054] According to one embodiment of the present invention, the transparent film may have an average step height of the surface curvature of 1 to 1,000 nm when the surface roughness of a 5 mm x 5 mm area is measured with an optical microscope. The average step height of the surface curvature may be preferably 1 to 100 nm, more preferably 1 to 80 nm, and most preferably 1 to 30 nm. When the transparent film has the average step height of the surface curvature as described above, spots such as optical stripes on the surface of the film depending on the light and angle are significantly reduced, and excellent surface quality can be provided.

[0055] According to one aspect of the present invention, the transparent film may have a curved region of 70% or less with respect to a total surface area of ​​5 mm x 5 mm. In this case, the curved region means a region where the average step Ra value of the surface curvature deviates from 30 nm when the step of a plane without curvature is set to zero (0) when measured with a confocal microscope. Specifically, the transparent film may have a curved region of 0.1 to 70% with respect to the total surface area. Preferably, the curved region may be 1 to 65% with respect to the total surface area, and more preferably, the curved region may be 1 to 62% with respect to the total surface area. In such a case, the projection spots due to the curved region can be reduced, and further, when the average step of the surface curvature described above is satisfied at the same time, the unevenness phenomenon can be reduced, and the display quality can be improved by improving visibility.

[0056] According to one aspect of the present invention, the transparent film may have a residual solvent content of 3 wt% or less based on the total weight of the film. Specifically, the transparent film may have a residual solvent content of 0.01 to 3 wt%, preferably 0.01 to 2 wt%, based on the total weight of the film. In this case, the residual solvent content is measured relative to the weight of the coating solution other than the solid content before drying. By having the residual solvent content as described above, it is possible to prevent deterioration of physical properties, and swelling or shrinkage due to the external environment does not occur, thereby further improving quality reliability.

[0057] According to one aspect of the present invention, the transparent film can be manufactured by adjusting the drying speed in the drying step after the solution casting step. The drying step can be adjusted to two or more steps, preferably three or more steps, to manufacture the film. For example, the drying step may measure the content of the residual solvent in the manufacturing solution of the transparent film, and vary the drying speed in each step, drying at a first drying speed in step 1, drying at a second drying speed in step 2, and drying at a third drying speed in step 3. The first to third drying speeds may be the same or different from each other. Preferably, the first to third drying speeds may be different from each other in order to prevent the occurrence of unevenness phenomenon in which spots occur on the surface of the film. In this case, the drying step is performed in order of steps 1 to 3.

[0058] More specifically, the first drying speed is 100 to 900 g / m 2 min, and the second drying speed is 10 to 400 g / m 2 min, and the third drying speed is 1 to 200 g / m 2 Preferably, the first drying speed is 300 to 900 g / m 2 min, and the second drying speed is 10 to 350 g / m 2 min, and the third drying speed is 10 to 150 g / m 2When the drying rate for the drying section is determined based on the content of the residual solvent as described above, the above-mentioned relations 1 and 2 can be satisfied, and the film surface does not substantially have unevenness, thereby realizing excellent appearance quality.

[0059] Preferably, in yet another embodiment, the drying step may be performed by adjusting the drying speed in four or more steps to produce a film. For example, the drying step may be performed by measuring the content of the residual solvent in the transparent film production solution, varying the drying speed in each step, and drying at a first drying speed in step 1, a second drying speed in step 2, a third drying speed in step 3, and a fourth drying speed in step 4. The first to fourth drying speeds may be the same or different from each other. In this case, the drying step is performed in the order of steps 1 to 4.

[0060] Preferably, the first to fourth drying rates may differ by three or more steps in order to prevent the occurrence of unevenness, which is a phenomenon of spots on the film surface. More preferably, the first to fourth drying rates may differ by three or more steps, and the different drying rates may have successively slower speeds.

[0061] More specifically, the first drying speed is 100 to 900 g / m 2 min, and the second drying speed is 10 to 400 g / m 2 min, and the third drying speed is 1 to 200 g / m 2 The fourth drying speed may be 1 to 150 g / m 2 Preferably, the first drying speed is 360 to 900 g / m 2 min, and the second drying speed is 10 to 350 g / m 2 min, and the third drying speed is 10 to 150 g / m 2 The fourth drying speed may be 10 to 130 g / m 2When the drying rate is set to the drying section depending on the content of the residual solvent as described above, the above-mentioned relations 1 and 2 can be satisfied, and the unevenness phenomenon on the film surface is substantially prevented, thereby achieving a better appearance quality.

[0062] According to one embodiment of the present invention, when the drying rate is three or more steps, it may satisfy the following formulas 1 and 2.

[0063] [Formula 1]

number

[0064] [Formula 2]

number

[0065] In the above formula 1 and formula 2, The V1 is the first drying speed (g / m 2 ·min), V2 is the second drying speed (g / m 2 ·min), V3 is the third drying speed (g / m 2 ·min).

[0066] Preferably, the formula 1 may satisfy 50 to 550, and the formula 2 may satisfy 20 to 280.

[0067] In still another embodiment, when the drying rate has four or more steps, the above formulas 1 and 2 are satisfied, and the following formula 3 is also satisfied.

[0068] [Formula 3]

number

[0069] In the above formula 3, The V3 is the third drying speed (g / m 2 ·min), V4 is the fourth drying speed (g / m 2 ·min).

[0070] Preferably, the formula 3 may satisfy 0-100.

[0071] When the drying rate satisfies the above-mentioned formulas 1 and 2 or formulas 1 to 3 as described above, the relational formulas 1 and 2 can be satisfied, the unevenness phenomenon on the film surface can be prevented, excellent appearance quality can be achieved, and the haze increase rate in harsh environments can be prevented.

[0072] In still another embodiment, when the drying speed has three or more steps, the following formula 4 may be satisfied.

[0073] [Formula 4]

number

[0074] In the above formula 4, The ΔV1 is the first drying speed (g / m 2 min) and second drying speed (g / m 2 ·min), and ΔV2 is the second drying speed (g / m 2 min) and the third drying speed (g / m 2 min), (V2-V3).

[0075] Preferably, the formula 4 satisfies 85-350, preferably 90-320.

[0076] As described above, when the drying speed satisfies the above formula 4, it is possible to significantly reduce fine unevenness on the surface and to further improve the appearance quality so that spots are substantially almost absent.

[0077] According to an embodiment of the present invention, the drying process may adjust the drying temperature, the amount of drying air, the speed of drying air, the temperature of the support, and the drying method in order to achieve a drying speed for each step.

[0078] According to one embodiment of the present invention, the transparent film may be provided with one or more drying regions during the drying process, preferably two or more, more preferably three or more, and most preferably four or more drying regions. In this case, the drying temperature, drying air volume, drying air speed, support temperature, drying method, etc. in each drying region may be changed according to the drying speed.

[0079] Specifically, in one embodiment, when the drying area is composed of three or more areas, the drying speed of each area can be made different so that the film moves through each area while drying. When the drying speed is adjusted according to the area as described above, the drying speed can be adjusted without a speed increase / decrease section due to the change in the drying speed, and fine unevenness on the surface can be significantly reduced and the appearance quality can be further improved.

[0080] According to one aspect of the present invention, the transparent film may be dried in a drying area having one or more nozzles selected from an impinged nozzle, a parallel flow nozzle, a venturi type nozzle, etc. As described above, by configuring various nozzles, the drying speed can be adjusted, and by adjusting the drying speed, the unevenness phenomenon in which spots due to color unevenness occur on the surface of the film can be minimized, and the transparent film can be used as an optical material with excellent appearance quality and improved visibility.

[0081] According to one embodiment of the present invention, the transparent film may have a thickness of 20 to 200 μm. The transparent film may preferably have a thickness of 20 to 150 μm, more preferably 20 to 100 μm. By having such a thickness, the above-mentioned relational expressions 1 and 2 can be satisfied, and excellent visibility without the occurrence of the unevenness phenomenon can be achieved.

[0082] Another aspect of the present invention is an optical material comprising the transparent film described above.

[0083] The transparent film according to the present invention is excellent as an optical material because it suppresses the phenomenon of unevenness that occurs during projection, has excellent appearance quality, and can provide excellent visibility.

[0084] The transparent film according to the present invention can be applied in a wide range of fields, including heat-resistant advanced materials such as automotive materials, aviation materials and spacecraft materials; and electronic materials such as insulating coating agents, insulating films, semiconductors and electrode protective films for TFT-LCDs; but is preferably applicable as an optical material in the display field, such as liquid crystal display devices.

[0085] Specifically, the present invention can be applied to the display field as various optical materials selected from a cover window film, a protective film, a retardation film, a diffusion film, a flexible substrate, a sealing material, a polarizer, and a touch panel substrate.

[0086] Yet another aspect of the present invention is a display device including the above-mentioned optical material. The display device includes the above-mentioned transparent film as an optical material, thereby minimizing eye fatigue of a user with excellent visibility.

[0087] According to one aspect of the present invention, the display device is applicable to any field that requires excellent optical properties, and is not particularly limited to a liquid crystal display, an organic electroluminescence display, an electronic paper, etc. Also, a display panel may be selected and provided according to the field of application. Specific examples include, but are not limited to, any one or more selected from a touch sensor panel, an organic light emitting display panel, a liquid crystal display panel, etc.

[0088] The transparent film, the optical material including the same, and the display device including the same according to the present invention will be described in more detail with reference to the following examples. However, the following examples are merely a reference for describing the present invention in detail, and the present invention is not limited thereto, and may be realized in various forms.

[0089] Furthermore, unless otherwise defined, all technical and scientific terms have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs. The terms used in the description of the present application are merely for the purpose of effectively describing a particular embodiment and are not intended to limit the present invention.

[0090] Furthermore, the unit of additives not specifically mentioned in the specification may be % by weight.

[0091] The physical properties of the present invention were measured as follows.

[0092] (1) Observation of the Projected Appearance (Mura) The appearance of the projection was observed by irradiating a 500mm x 500mm film with a HID (High Intensity Discharge) lamp so that it was projected perpendicularly. The projected image was projected onto a white back board, and the projected image was confirmed with the naked eye. The positions of the lamp, film, and back board were adjusted so that the projected image was in focus. When checking for mura, a NG / OK rating was given depending on the size and degree of recognition of the mura, and it was deemed NG when the mura was 2mm or more wide to the naked eye and had a clear shape.

[0093] (2) T and θ The transmittance and linear retardance of the polarized color generated by the polarization generator (PSG) were measured using Axoscan equipment manufactured by Axometrics. In particular, T was measured as the relative transmittance when the transmittance of a film with a retardation of 1° or less and the same refractive index was calculated as 100%.

[0094] (3) Average surface curvature step and curvature area The transparent films of the examples and comparative examples were observed using a 3D shape measuring device (Keyence, VK-X1050). The surface roughness (Ra) value of the film was measured over an area equivalent to 5 mm x 5 mm. In this case, the film was fixed so that it would not peel off from the substrate during measurement, and then the measurement was performed. The surface roughness values ​​of 15 adjacent areas were measured using the same method, and the average value was calculated. For a 5 mm x 5 mm area of ​​the film, when the step of a flat surface without bending was set to zero (0) when measuring with a confocal microscope, the area (%) of the bent part was calculated using the following formula 5.

[0095] [Formula 5] {area of ​​region where roughness value is 80-120% of average roughness value (Ra)} / {area of ​​total region}×100%

[0096] (4) Drying speed measurement The drying rate in the dryer was calculated by measuring the residual solvent in the film that had passed through each drying zone. The residual solvent content was measured by weight A at 150°C using a TGA (TA, Discovery). 150 Weight A at 370℃ 370 The value obtained by subtracting the above was determined to be the residual solvent in the film. In this case, the measurement conditions were that the temperature was raised to 400°C at a rate of 30°C / min, and the change in weight was measured in the range of 150 to 370°C.

[0097] [Production Example 1] [TFMB:6FDA:TPC molar ratio = 100:14:86] Dimethylacetamide (DMAc) and 2,2'-bis(trifluoromethyl)-benzidine (TFMB) were added to a reactor in a nitrogen atmosphere and thoroughly stirred, and then 4,4'-hexafluoroisopropylidenediphthalic anhydride (6FDA) was thoroughly stirred until it was dissolved. Next, terephthaloyl dichloride (TPC) was added and stirred for 6 hours to dissolve and react, producing a polyamic acid resin composition. At this time, the amount of each monomer was TFMB:6FDA:TPC in a molar ratio of 100:14:86, and the temperature of the reactor was maintained at 30°C. The viscosity of the finally obtained polyamic acid resin composition was 33,000 cps. Next, pyridine and acetic anhydride were added to the polyamic acid resin composition in an amount 2.5 times the total amount of dianhydride added, and the mixture was stirred at 60°C for 1 hour to produce polymerization liquid 1.

[0098] Next, the polymerization solution 1 was precipitated in an excess amount of methanol, and the solid matter obtained by filtration was vacuum dried at 50° C. for 6 hours or more to obtain polyamideimide. The weight average molecular weight of the finally obtained polyamideimide was 106,000 g / mol.

[0099] [Production Example 2] [TFMB:CBDA:IPC molar ratio = 100:60:40] Dimethylacetamide (DMAc) and 2,2'-bis(trifluoromethyl)-benzidine (TFMB) were added to a reactor in a nitrogen atmosphere and thoroughly stirred, and then 4,4'-cyclobutanetetracarboxylic dianhydride (CBDA) was thoroughly stirred until it was dissolved. Next, isophthaloyl dichloride (IPC) was added and stirred for 6 hours to dissolve and react, producing a polyamic acid resin composition. At this time, the amount of each monomer was TFMB:CBDA:IPC molar ratio = 100:60:40, and the temperature of the reactor was maintained at 30 ° C. The viscosity of the finally obtained polyamic acid resin composition was 90,000 cps. Next, pyridine and acetic anhydride were added to the polyamic acid resin composition in an amount 2.5 times the total amount of dianhydride added, and the mixture was stirred at 60 ° C. for 1 hour to produce polymerization liquid 2.

[0100] Next, the polymerization solution 2 was precipitated in an excess amount of methanol, and the solid matter obtained by filtration was vacuum dried at 50° C. for 6 hours or more to obtain polyamideimide. The weight average molecular weight of the finally obtained polyamideimide was 310,000 g / mol.

[0101] [Production Example 3] [TFMB:CBDA:IPC molar ratio = 100:40:60] Dimethylacetamide (DMAc) and 2,2'-bis(trifluoromethyl)-benzidine (TFMB) were added to a reactor in a nitrogen atmosphere and thoroughly stirred, and then 4,4'-cyclobutanetetracarboxylic dianhydride (CBDA) was thoroughly stirred until it was dissolved. Next, isophthaloyl dichloride (IPC) was added and stirred for 6 hours to dissolve and react, producing a polyamic acid resin composition. At this time, the amount of each monomer was TFMB:CBDA:IPC molar ratio = 100:40:60, and the temperature of the reactor was maintained at 30 ° C. The viscosity of the finally obtained polyamic acid resin composition was 68,000 cps. Next, pyridine and acetic anhydride were added to the polyamic acid resin composition in an amount of 2.5 times the total amount of dianhydride added, and the mixture was stirred at 60 ° C. for 1 hour to produce polymerization liquid 3.

[0102] Next, the polymerization solution 3 was precipitated in an excess amount of methanol, and the solid matter obtained by filtration was vacuum dried at 50° C. for 6 hours or more to obtain polyamideimide. The weight average molecular weight of the finally obtained polyamideimide was 180,000 g / mol.

[0103] The obtained polymerization liquid was cast on a glass substrate using a slot die, and then dried under the following drying conditions to obtain a transparent film with a thickness of 30 to 80 μm. The type of polymerization liquid used, the configuration of the drying nozzle, and the configuration based on the drying speed are as shown in the examples and comparative examples in Table 1 below.

[0104] [Table 1]

[0105] The physical properties of the examples and comparative examples shown in Table 1 were measured and are shown in Table 2 below.

[0106] [Table 2]

[0107] As shown in Table 2, it was confirmed that the transparent film according to the present invention has excellent appearance characteristics with almost no color unevenness, which is a phenomenon in which the color is not uniform but appears as spots, by satisfying the relational expressions 1 and 2. Furthermore, this can be achieved by satisfying a specific drying speed range. In addition, by satisfying the relational expressions 1 and 2, the curved area is reduced, and spots such as optical stripes on the surface of the film due to light and angle are significantly reduced, providing excellent surface quality.

[0108] Furthermore, it was confirmed that in Examples 4, 6, 7 and 8, which all satisfy the above formulas 1 to 4, the unevenness phenomenon on the film surface was substantially eliminated compared to the other Examples, and a more excellent appearance quality could be achieved.

[0109] As a result, the transparent film according to the present invention can be used as an optical material with minimized unevenness, excellent appearance quality, and improved visibility.

[0110] The present invention has been described above using specific details and limited examples, but these are provided to facilitate a general understanding of the present invention. The present invention is not limited to the above examples, and various modifications and variations can be made from such descriptions by those having ordinary knowledge in the field to which the present invention pertains.

[0111] Therefore, the concept of the present invention should not be limited to the above-described embodiments, and all modifications equivalent to or equivalent to the scope of the present claims, as well as the scope of the claims described below, are considered to fall within the scope of the concept of the present invention.

Claims

1. A transparent film in which, when one polarized light is transmitted through the film, the light that is generated contains a mixture of two waves and satisfies the following relations 1 and 2. [Relationship 1] [0010] [Relationship 2] [0025] In the above Relational Formulas 1 and 2, The T is the sum of the amplitudes when two waves of transmitted light interfere with each other, the A is the wave amplitude of polarized light, and the θ is the phase delay angle (°) of the wave that travels along the slow axis of the transparent film.

2. The transparent film according to claim 1 , which is a polyimide-based film.

3. 2. The transparent film according to claim 1, wherein the average step height of the surface curvature is 1 to 1,000 nm.

4. 2. The transparent film according to claim 1, wherein the curved area is 70% or less of the total surface area.

5. 2. The transparent film of claim 1, having a thickness of 20 to 200 μm.

6. 2. The transparent film according to claim 1, wherein the residual solvent content is 3% by weight or less based on the total weight of the film.

7. 2. The transparent film according to claim 1, wherein the drying of the transparent film is performed in a drying area including at least one nozzle selected from the group consisting of an impinged nozzle, a parallel flow nozzle, and a venturi type nozzle.

8. An optical material comprising the transparent film according to any one of claims 1 to 7.

9. A display device comprising the optical material of claim 8.